UJI AKTIVITAS ANTI BAKTERI EKSTRAK ETANOL DAUN BINAHONG (Andera Cordifolia) TERHADAP BAKTERI Stahpylococcus Aureus - Isfanda Isfanda; Rizarullah Rizarullah (Jurnal Sains Riset, 2021)
Antibacterial is a compound that can be used for the treatment of infections caused by bacteria. Traditionally Binahong plants (Anredera cordifolia) are plants known to the public to handle various diseases. Binahong leaf that has antibacterial natural compounds such as oleanolic acid, ursolic acid and apigenin. This study aims to examine the antibacterial activity of ethanol extract of binahong leaves against staphylococcus aureus bacteria. This research is using experimental method. Leaves binahong obtained from Sawang Aceh Utara. The maceration stage is done by using ethanol 96% for 3 days and then in doing phytochemical test to find out secondary metabolic content. Antibacterial testing using discs. The results of phytochemical tests found secondary metabolic compounds class of alkaloids, polyphenols, saponins, quinones, and triterpenoids. Antibacterial test using 25%, 50%, 75% concentration, negative control (Aquadest), and Positive control (Amoxicillin) obtained the results are 6mm, 6mm, 6.67mm, 0mm, 30,67 mm. Based on the research of ethanol extract of binahong leaf has an inhibitory power to the growth of Staphylococcus Aureus bacteria at 75% concentration. At concentrations of 25% and 50% there was no inhibition zone of Staphylococcus aureus bacteria growth.Keywords: Antibacterial, daun binahong, staphylococcus aureus